Kembali Menyoal Tentang Ineransi Alkitab - Hadi P. Sahardjo (Sekolah Tinggi Teologi SAPPI Ciranjang, 2016)
The word “innerancy” can be defined as “the quality of free from error” in the Bible. The innerancy taught that the Bible free from error. It cannot be false and not state something counter to Rene Pache mention two term can actually interchangeable place, namely innerancy and infability, there are some people who are trying to opposed the doctrine of innerancy and infability, even though both the doctrine is essetially teach the same thing about the scripture, that the scripture is absolutely right, impeccable.